Tinjauan Yuridis Tentang Dispensasi Perkawinan di Indonesia - Ariyanti, Siska; Kusnadi, Sekaring Ayumeida (Legal Standing : Jurnal Ilmu Hukum, 2025)
Child marriage in Indonesia is a complex issue with socio-cultural dimensions and human rights violations. Although Law No. 16/2019 stipulates that the maximum age of marriage is 19 years old, the implementation of the child marriage recognition system still allows minors to marry due to pregnancy outside of marriage or due to social pressure. The purpose of this study is to evaluate the legal analysis of legislation related to the exclusion of the age of marriage and its implementation. The method used is normative research with a legal conceptual approach. The findings show that despite strict regulations, gaps in the exemption application process continue to create the potential for child marriage. Therefore, measures are needed to tighten the procedure, such as raising the minimum age limit, implementing additional documentation requirements, and making marriage counseling mandatory. This tightening is expected to protect children's rights, raise public awareness of the negative impacts of early marriage, and increase interest in education and mental preparation before marriage.